Association between Bone Mineral Density and Platelet Indices in Postmenopausal Women - Adem Yıldırım; Hacı Taner Bulut (Galenos Yayinevi, 2016)
Objective: It was shown that low bone mass is associated with increased cardiovascular mortality in early and late menopausal period. The aim of this study was to investigate the relationship between bone mineral density (BMD) and platelet indices (mean platelet volume [MPV], platelet distribution width [PDW] and platelet count [PC]) in postmenopausal women. Materials and Methods: We retrospectively investigated BMD and platelet parameters of the women aged between 55-75 years between January 2012-December 2015 and 311 women meeting study criteria were included in the study. Participants were divided into 3 groups (control, osteopenia, osteoporosis groups) according to BMD parameters. The average values of age, BMD and platelet indices of groups were compared. Potential correlations between platelet indices with age and BMD levels were investigated and the correlation level and direction were investigated when age variable was controlled. Results: Participants in osteopenia and osteoporosis groups had significantly higher OPH values than those in the control group (p=0.002). When age variable controlled, there was a weak and negative correlation between OPH and with lumbar, femoral neck and femur total BMD (r=-0.177, p=0.002; r=-0.160, p=0.005; r=-0.151, p=0.008 respectively). On the other hand, there was no significant relationship between BMD with PC or PDW. Conclusion: The results of this study showed that there is a weak and negative correlation between the BMD the MPV. Further studies on osteoporosis and platelet indices, may contribute to better understanding of increased thrombotic risk in postmenopausal period.